Pubertal development in white and coloured urban schoolgirls - Thomas, Carol Ann (Department of Obstetrics and Gynaecology, 2017)
The aim of this study was to compare pubertal development between the two main ethnic groups in the Cape, controlling for social class. This study aimed to investigate: 1. The age of menarche and other stages of pubertal development of white and coloured school girls living in greater Cape Town. 2. The relationship between the age of menarche and the other stages of pubertal development, social class and race. 3. The influence of home environment (childminder, sibling number, maternal education) on onset of menarche and breast development. This data further contributes to a larger study on pubertal development of all representative ethnic groups and social classes in the Cape. Our hypothesis is that social class, and not race, is a major determinant of pubertal development.